Climatic Conditions in the Western and Northern Cordillera During the Last Glaciation: Paleoecological Evidence - Mathewes, Rolf (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1991)
ABSTRACTIn the southern Cordillera, paleoecological evidence suggests that climate was variable, from cooler than present by up to 3°C, to possibly similar to modern during the Olympia non-glacial interval (> 59 TO 25-29 ka). The development of open subalpine parkland vegetation in lowlands after 25 ka reflects slow cooling to glacial conditions. Assumptions about continuously cold and dry glacial conditions are tested and disputed. Between 18-19 ka, pollen, plant macrofossil and beetle evidence suggest relatively warm and moist conditions in the Fraser/Puget Lowlands. A tentative correlation can be inferred with the recently defined "Hanging Lake thermal event" around 18-22 ka in the unglaciated Yukon. Further work should be done to test this inference. Paleobotanical data suggest that increasing moisture, rather than increased cooling, was responsible for the late Vashon ice advance in the southwestern Cordillera. The controversy regarding the nature of the vegetation cover in eastern Beringia, north of the main Cordilleran ice sheet, is not yet settled, although evidence to date favours a complex mosaic of tundra and "steppe-tundra" plant communities supporting a greater diversity of grazing large mammals than exist in the area today.